Vascular development - Birdsey, Graeme (Henry Stewart Talks, 2026)
Vascular system, Angiocrine factors, Tip cells, Stalk cells, Sprouting, Angiogenesis, Vascular remodeling, Anastomosis, Hypoxia, Cell migration, Lateral inhibition, Quiescence